Soil-driven physiological and biometric traits in Ceiba pentandra (L. Gaertn) via cleft grafting and seed propagation in Southern India - Banoo, R; Murugesh, M; Vaiyapuri, K; Rajagopal, B; Balamurugan, J; Sekar, I; Sujatha, K B; Yadav, N (Plant Science Today, 2025)
Ceiba pentandra, a multipurpose tree species, is widely utilized in agroforestry and afforestation projects. Evaluating its growth in diverse soil types via sexual and asexual propagation is essential for its promotion in various ecological regions. Thus, the current study was carried out to assess the growth of kapok in Tamil Nadu black soil and red laterite soil. Seeds for sexual propagation and scion wood for asexual propagation (cleft grafting) of Ceiba pentandra were obtained from four superior trees in Coimbatore and Theni districts. Six-month-old nursery-raised seedlings were used as rootstock. Seeds were sown and cleft grafting was conducted in February 2023. Both seedlings and grafts were transplanted to two study locations in September 2023. Significant variations in biometric parameters among different sources, soil types and propagation techniques were observed. CP-29 ramet recorded maximum height, volume index, greater photosynthetic rate and relative water content. Significant correlations between growth attributes and physiological traits were documented in the current study. Positive correlation between photosynthetic rate, number of leaves and stomatal conductance were noted. Principal component analysis (PCA) revealed that principal component 1 (PC1) accounted for 59.7% of the total variability and PC2 accounted for 35.1%. Ramets established through cleft grafting in black soil have shown favourable growth. Thus, the CP29 and MTP01 exhibited superior performances based on growth traits.